2018
DOI: 10.1016/j.jbiomech.2018.04.019
|View full text |Cite
|
Sign up to set email alerts
|

On the variation in maternal birth canal in vivo viscoelastic properties and their effect on the predicted length of active second stage and levator ani tears

Abstract: The pubovisceral muscles (PVM) help form the distal maternal birth canal. It is not known why 13% of vaginal deliveries end in PVM tears, so insights are needed to better prevent them because their sequelae can lead to pelvic organ prolapse later in life. In this paper we provide the first quantification of the variation in in vivo viscoelastic properties of the intact distal birth canal in healthy nulliparous women using Fung's Quasilinear Viscoelastic Theory and a secondary analysis of data from a clinical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Viscoelastic properties of the distal birth canal have been suggested as a strong contributor to the time a mother needs to push in the second stage to deliver the fetal head. 31 Previous studies used transperineal ultrasound to investigate the relation between antenatally assessed pelvic organ mobility on Valsalva and levator ani hiatal dimensions in the prediction of outcome of labor and reported that reduced mobility and smaller levator ani hiatal dimensions are associated with increased risk of operative delivery. 33e35 However, other authors did not find any association between pelvic floor dimensions and the mode of delivery.…”
Section: Comparison With Results Of Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Viscoelastic properties of the distal birth canal have been suggested as a strong contributor to the time a mother needs to push in the second stage to deliver the fetal head. 31 Previous studies used transperineal ultrasound to investigate the relation between antenatally assessed pelvic organ mobility on Valsalva and levator ani hiatal dimensions in the prediction of outcome of labor and reported that reduced mobility and smaller levator ani hiatal dimensions are associated with increased risk of operative delivery. 33e35 However, other authors did not find any association between pelvic floor dimensions and the mode of delivery.…”
Section: Comparison With Results Of Previous Studiesmentioning
confidence: 99%
“…24,26,28e30 Indeed, it has been suggested that the viscoelastic properties of the intact distal birth canal in healthy nulliparous women may predict the duration of the second stage of labor. 31 However, the effect of levator ani muscle coactivation on labor outcome in women undergoing induction of labor has not been previously assessed.…”
Section: Introductionmentioning
confidence: 99%
“…They directly tested that idea using a computer model based on the published variations in the two parameters constituting the Capacity-Demand ratio. They used a similar approach for the risk for risk of levator injury which they refined in a follow-up paper, Tracy et al [ 4 ] by adding actual measures of distal maternal birth canal tissue elasticity and viscosity during the first stage of labor to predict the length of the active second stage of labor and risk for levator injury, both goals of the Gan et al paper.…”
mentioning
confidence: 99%